배우자 사별을 경험한 중년여성 건강 관련 삶의 질 영향요인 –8기 3차년도(2021년) 국민건강영양조사 이차자료분석 - 장현정(Hyun-Jung Jang) (한국콘텐츠학회 논문지, 24(4), 2024)
본 연구는 국민건강영양조사의 8기 3차년도(2021년) 단일자료를 이용하여 배우자 사별을 경험한 중년여성의 건강 관련 삶의 질에 영향을 미치는 요인을 확인하기 위한 복합표본 이차분석연구이다. 연구대상자는 표면에 노출되는 것을 꺼려하는 특성을 고려하여 55명 수집되었고, 자료는 SPSS 27.0 프로그램으로 복합표본 빈도분석 및 기술통계, T-Test, ANOVA, 복합표본 일반선형모형 회귀분석을 사용하였다. 연구 결과 배우자 사별을 경험한 중년여성의 건강 관련 삶의 질에 영향을 미치는 요인으로 교육수준, 우울, 스트레스 인지로 나타났으며 이에 대한 설명력은 56.3%이었다(F=20.324, p=.000). 배우자 사별을 경험한 중년여성의 건강 관련 삶의 질 향상을 위해서는 교육수준이 낮은 집단을 위험집단으로 인식하고 스트레스와 우울 관리방법을 대상자의 특성에 따라 맞춤식 프로그램으로 개발하고, 적용해야 할 것이다. This study is a secondary analysis study to identify the factors affecting health-related quality of life of middle-aged women who experienced spouse bereavement using single-year data from the 3rd year(2021)of the 8th Korea National Health and Nutrition Examination Survey. 55 subjects were collected in consideration of the characteristics of reluctance to be exposed to the surface, and the data were the SPSS 27.0 program, using complex sample frequency analysis, descriptive statistics, T-Test, ANOVA, and complex sample general model regression analysis using the SPSS 27.0 program. As a result of the study, ‘Education level’, ‘Depression’, and ‘Perceived Stress’ were found to be factors affecting the health related quality of life of middle-aged women who experienced spouse bereavement, and 56.3% of them had explanatory power (F=20.324, p=.000). In order to improve the health-related quality of life of middle-aged women who have experienced spouse bereavement, low-educated groups should be recognized as risk groups, and stress and depression management methods should be developed and applied as customized programs according to the characteristics of the subjects. KCI Citation Count: 0